Conservation of Protected Areas in Federal System, How? (The Initiation, 2010)
The formal conservation history of Nepal is relatively shorter one. The protection and conservation of National Parks, Wildlife Reserves, Conservation Areas and Buffer Zone are creating a burning debate amongst all stakeholders along with the debate of the state restructuring. The federal system of Nepal is quite different compare to other countries. All the rational designed in the face of unitary governance system needs a redefinition now. We have to create a suitable road-map for the division power among different levels of governments using the general orientation of international conservation framework. Constitutional provision should be designed in such a way that there should be little political intervention on natural resources. Mostly the National Parks and Wildlife Reserves are listed under the jurisdiction of federal government in federal countries. Environment has been a matter of concurrent power among many other federal countries. In Nepal, there is a growing consensus in favor of federal responsibility for the large infrastructures based on their inter-provincial importance, impact and extent. National Parks, Wildlife Reserves, Buffer Zones and Conservation Areas should be matter of concurrent authority where the federal government makes a framework policy but works in collaboration with the provincial government and local communities when it comes of implementing it. This will be the only way where by federal government could comply with the international commitments. Similarly, provincial government can implement the conservation functions with the support of local communities, indigenous people and groups dependent on the natural resource. The framework for such mechanism should be designed through an extensive consultation with the key stakeholders during the formulation of legislation and bylaws following the promulgation of the new constitution.The full text of the article is in Nepali. DOI: 10.3126/init.v3i0.2518 The Initiation Vol.3 2009 p.161-166